(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the efficacy of Hyoscine-N-butylbromide versus drotaverine hydrochloride in the augmentation of labor. Study Design: Double-blind, randomized controlled trial study Place and Duration of Study: This study was conducted at the Gynecology Unit-I, Liquate University Hospital Hyderabad for the period of one year from February 2018 to January 2019. Materials and Methods: This study was conducted on 270 women to compare the efficacy of Hyoscine-N-butyl bromide versus drotaverine hydrochloride in the augmentation of labor Gynecology Unit-I Liquate University Hospital Hyderabad. Women of reproductive age group between 18-35 years and gestational age between 37-40 weeks were included. All the data was analyzed in SPSS version 22.0. Results: The average age of the patients was 21.45±5.42 years. Efficacy was significantly high in the drotaverine hydrochloride group than the Hyoscine-N-butylbromide group (73% vs. 41.8% p=0.0005). Conclusion: Drotaverine hydrochloride appears to be effective in accelerating the first stage of labor.